2012
DOI: 10.1007/s00277-012-1412-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin levels and endocrinopathy in medically treated patients with β thalassemia major

Abstract: The association between iron overload indices and pathology of the heart and liver in transfusion-dependent patients with β thalassemia major (TM) has been extensively studied. Nonetheless, data on endocrine disease remains limited. This was a cross-sectional study of 382 TM patients treated with regular transfusions and desferrioxamine at the Thalassemia Center in Dubai, UAE. Retrieved data included demographics, splenectomy status, steady-state serum ferritin levels, and the presence of endocrinopathies (dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 46 publications
(59 reference statements)
2
65
0
3
Order By: Relevance
“…7 Serum ferritin levels in medically treated patients with β thalassemia major was studied by Belhoul KM et al The association between iron overload indices and pathology of the heart and liver in transfusion-dependent patients with β thalassemia major has been extensively studied. 8 The mean value of serum ferritin was increased and these results were in close collaboration with the results obtained by Mishra AK et al These levels reflect inadequate chelation and vulnerability to develop iron overload related complications. There is an urgent need to rationalize the chelation therapy and to create awareness about the consequences of iron overload in the patients.…”
Section: Discussionsupporting
confidence: 85%
“…7 Serum ferritin levels in medically treated patients with β thalassemia major was studied by Belhoul KM et al The association between iron overload indices and pathology of the heart and liver in transfusion-dependent patients with β thalassemia major has been extensively studied. 8 The mean value of serum ferritin was increased and these results were in close collaboration with the results obtained by Mishra AK et al These levels reflect inadequate chelation and vulnerability to develop iron overload related complications. There is an urgent need to rationalize the chelation therapy and to create awareness about the consequences of iron overload in the patients.…”
Section: Discussionsupporting
confidence: 85%
“…A cross-sectional study of 382 BTM patients treated with regular transfusions and desferrioxamine, demonstrated that patients with serum ferritin level >2,500 ng/ml were 3.53 times (95% CI 1.09 11.40) more likely to have DM [36]. Some studies have also reported that ferritin levels of patients with DM were not significantly different from those patients who had no DM [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transfusions can lead to the accumulation of excessive iron in the body which needs to be corrected using chelating agents to remove excess iron by excretion [15].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin levels of greater than 2500 μg/l are known to have high rates of iron overload-related complications [15]. But individuals with Cys282Tyr homozygosity might present with abnormal iron tests with or without clinical symptoms and with or without proving evidence of iron overload [27].…”
Section: Discussionmentioning
confidence: 99%